2013
DOI: 10.1097/tin.0b013e31828d7a61
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Diet Quality of a Type 2 Diabetes Sample Using the Healthy Eating Index 2005

Abstract: The purpose of this cross-sectional study was to evaluate the diet quality of a sample of individuals with type 2 diabetes, using the Healthy Eating Index 2005, and to determine differences in total and component scores among clinical and demographic characteristics. Participants were recruited from clinics at a large, urban medical center. Each participant (n = 99) completed three to four 24-hour recalls and a demographics questionnaire. Foods were converted to MyPyramid servings to create Healthy Eating Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Also, in Coltman's study, it was observed that older people had a higher HEI score compared to the patients between 40 and 60 years old. Their results were consistent with ours [ 21 ]. Also, in a study carried out by Patricia Guenther, the mean score of HEI-2010 was lower in younger adults compared to older adults; the obtained results were similar to both editions of HEI (HEI-2005 and HEI-2010) [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…Also, in Coltman's study, it was observed that older people had a higher HEI score compared to the patients between 40 and 60 years old. Their results were consistent with ours [ 21 ]. Also, in a study carried out by Patricia Guenther, the mean score of HEI-2010 was lower in younger adults compared to older adults; the obtained results were similar to both editions of HEI (HEI-2005 and HEI-2010) [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…We observed fair diet quality scores in our cohort similar to other studies reporting scores ranging from 40.2 to 58.8, with poor intake of wholegrains, dairy, fruits and vegetables. 34,35 In Singapore, the promotion of wholegrains, fruits and vegetables is ubiquitous among public diabetes-related health messages, guidelines and education. 26 However, our findings suggest that these health promotional messages may not necessarily be translated into ‘process knowledge’ in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with cross-sectional data from 2018 that found an inverse association between diet quality (measured by DASH score) and obesity in 211 Chinese adults (54.5% male) with T2D 27 . Similarly, a 2013 cross-sectional study of 99 adults (27.3% male) with T2D in the United States (US) found that individuals who were of normal weight or overweight, had a significantly higher diet quality (measured by Healthy Eating Index score) than those who were obese 29 . The present study has advanced upon these cross-sectional studies by investigating changes in diet quality over time, suggesting that male patients who have a higher BMI at diagnosis may find dietary change more difficult than those who start off with lower mean BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Diet quality has been shown to be inversely associated with rates of obesity [26][27][28][29] . In the present study, men who did not improve their diet quality by 3 months had a significantly higher baseline BMI than men who improved their diet quality (p = 0.048).…”
Section: Discussionmentioning
confidence: 99%